2021
DOI: 10.5937/jomb0-26839
|View full text |Cite
|
Sign up to set email alerts
|

Association of fibrinogen and plasmin inhibitor, but not coagulation factor XIII gene polymorphisms with coronary artery disease

Abstract: Background: In the final phase of cloth formation, fibri(noge)n constitutes frame whereas factor XIII (FXIII) active form is responsible for the covalent cross-linking of fibrin fibers and plasmin inhibitor (PI), thus contributing to clot stability. It could be expected that any change of coagulation factors’ structure affects the clot formation and modulate the atherothrombotic risk. The aim was to determine the frequency of four single nucleotide polymorphisms: (i) A>G in codon 312 of the fibrinogen α-cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
1
3
0
Order By: Relevance
“…In over-dominant genetic model, MMP3 -1612 5A/6A was a risk factor for CAD. Inconsistent with our findings, a relevant study reported that morbid risk and progression risk are higher in subjects carrying MMP3 -1612 6A homozygous than those carrying MMP3 -1612 5A homozygous [32] . Xu et al [33] suggested that MMP3 and MMP9 mutations could be utilized as hallmarks for predicting susceptibility to CAD.…”
Section: Discussionsupporting
confidence: 86%
“…In over-dominant genetic model, MMP3 -1612 5A/6A was a risk factor for CAD. Inconsistent with our findings, a relevant study reported that morbid risk and progression risk are higher in subjects carrying MMP3 -1612 6A homozygous than those carrying MMP3 -1612 5A homozygous [32] . Xu et al [33] suggested that MMP3 and MMP9 mutations could be utilized as hallmarks for predicting susceptibility to CAD.…”
Section: Discussionsupporting
confidence: 86%
“…Specifically, Met-α2AP (Arg6) was cleaved about eight times more rapidly than Met-α2AP (Trp6) [36]. Recently, Bronic et al have shown in a Croatian cohort that individuals with Arg6Trp α2AP CC genotype had an almost 4-fold higher risk of coronary artery disease compared with Arg6Trp α2AP TT genotype [37].…”
Section: Alpha-2 Antiplasmin (α2ap)mentioning
confidence: 99%
“…However, no such protection was observed against coronary artery disease (CAD) and myocardial infarction (MI). In a recent study on the potential association of the polymorphism (pR6W, rs2070863) with CAD and MI, Bronic and colleagues reported that patients with R6W PI CC genotype had 3.86 times higher odds ratio of risk factor for the CAD than the patients with R6W PI TT genotype in a group of Croatian patients [45].…”
Section: Accepted Manuscriptmentioning
confidence: 99%